Le donne della Tavola Periodica - Venturi, Margherita (Chimica nella Scuola, 2025)
A topic related to the Periodic Table that is rarely addressed concerns its “female face”, that is, the contribution that women have made in adding new boxes to accommodate new elements. Marie Curie, who discovered radium and polonium, is certainly known to everyone, but the list is long and includes female scientists of great value, often forgotten. Some of them are remembered in this article.